2012
DOI: 10.1016/j.bbrc.2012.04.127
|View full text |Cite
|
Sign up to set email alerts
|

Modifications on the hydrogen bond network by mutations of Escherichia coli copper efflux oxidase affect the process of proton transfer to dioxygen leading to alterations of enzymatic activities

Abstract: We have the pleasure for submitting our manuscript entitled "Modifications on the Hydrogen Bond Network by Mutations of Escherichia coli CueO Affect the Process of Proton Transfer to Dioxygen Leading to Peculiar Alterations of Enzymatic Activities" inBiochemical Biophysical Research Communications. CueO is the cuprous oxidase from Escherichia coli and concerns in a system to excrete excess copper to protect E. coli from oxidative damages. Together with laccase and related enzymes, CueO is a multiocopper oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We have performed studies on a MCO, Escherichia coli CueO [5][6][7][8][9] at the aims of revealing its structure-function relationships and of applying it to biofuel cells and pigment formations as catalyst [10,11]. The T1Cu site in CueO becomes unoccupied as a result of the mutation at the Cys ligand with with O 2 because one electron is deficient to form two water molecules [5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed studies on a MCO, Escherichia coli CueO [5][6][7][8][9] at the aims of revealing its structure-function relationships and of applying it to biofuel cells and pigment formations as catalyst [10,11]. The T1Cu site in CueO becomes unoccupied as a result of the mutation at the Cys ligand with with O 2 because one electron is deficient to form two water molecules [5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cu 2+ ion has never been incorporated into the T1Cu site, of which Cys ligand is changed to Ser [2,[5][6][7][8][9].…”
Section: Based On Spectral Property and Enzymatic Reactivity The Restmentioning
confidence: 99%
“…Averaged Cu contents in the single and double mutants were 4 and 3, respectively, within the experimental error of 10% (Table 1). The single mutants, Glu463Gln and Glu463Ala exhibited very low enzymatic activities, although the corresponding Ala mutants of CueO and Fet3p showed considerably high enzymatic activities [19,23]. On the other hand, the double mutants did not show enzymatic activities due to the mutation at the T1Cu site [12].…”
Section: Characterizations Of Mutantsmentioning
confidence: 99%
“…Mutations on the conserved Glu residue have been performed for CueO and Fe3p, resulting in the successful trapping and characterization of the intermediate II [11,19,21]. Mutations of this Glu residue with Gln led to practically complete loss in enzymatic activities, but its substitution with Ala exhibited considerably high enzymatic activities due to a formation of compensatory hydrogen bond network with only water molecules [19,23,24], while it was found that Asp located in one of other two channels leading to TNC also concerns profoundly in the formation of water molecules [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…presents unequivocal evidence that the hydrogen bond between Asp439 and His443 functions as an electron-transfer pathway. 8,15 Nevertheless, the hydrogen bond is not the exclusive electron-transfer pathway, as judged from the fact that the copper(I) oxidase activity has been reserved in the Asp439Ala mutants by ca. 50% from those of the parent enzymes.…”
mentioning
confidence: 99%